A Whale of a Tale: A One Environmental Health Approach to Study Metal Pollution in the Sea of Cortez. - Wise, John Pierce (Toxicol Appl Pharmacol, 2019)
Marine metal pollution is an emerging concern for human, animal, and ecosystem health. We considered metal pollution in the Sea of Cortez, which is a relatively isolated sea rich in biodiversity. Here there are potentially significant anthropogenic inputs of pollution from agriculture and metal mining. We considered the levels of 23 heavy metals and selenium in seven distinct cetacean species found in the area. Our efforts considered two different periods of time: 1999 and 2016/17. We considered the metal levels in relation to (1) all species together across years, (2) differences between suborders Odontoceti and Mysticeti, (3) each species individually across years, and (4) gender differences for each of these comparisons. We further compared metal levels found in sperm whale skin samples collected during these voyages to a previous voyage in 1999, to assess changes in metal levels over a longer timescale. The metals Mg, Fe, Al, and Zn were found at the highest concentrations across all species and all years. For sperm whales, we observed decreased metal levels from 1999 to 2016/2017, except for iron (Fe), nickel (Ni), and chromium (Cr), which either increased or did not change during this time period. These results indicate a recent change in the metal input to the Sea of Cortez, which may indicate a decreased concern for human, animal, and ecosystem health for some metals, but raises concern for the genotoxic metals Cr and Ni. This work was supported by NIEHS grant ES016893 (J.P.W.) and numerous donors to the Wise Laboratory.